Design and Construction of Inverse Time & Definite Time Overcurrent Relay Based on Arduino Uno - susilo, rizky; Handri Gunanto, Lucianus; Ipniansyah, Ipniansyah; Abdurrahim, Abdurrahim; Nugroho, Toto; Fikri Fadhillah, Gusti; Ary Sandy Saputra, Muhammad (Universitas Muhammadiyah Surakarta, 2026)
This system is designed to detect overcurrent faults, then disconnect them from the circuit. In inverse time overcurrent relay, the relay trip time will depend on the magnitude of the fault current. The greater the fault current, the shorter the relay trip time will be. Meanwhile, in definite time overcurrent relay, the relay trip time will work according to the specified time. This system consists of Arduino Uno, PZEM-004T, and relay module. PZEM-004T acts as a current sensor that can measure the current value flowing in the load. Arduino Uno is used as a microcontroller that can process data that has been measured through PZEM-004T. Then, if the current flowing in the load has exceeded the specified value, the Arduino Uno will activate the relay that can disconnect the current flowing in the load. The system was tested using an induction motor and variable resistor. The test results show that this system works effectively and efficiently, and can protect the load from damage due to overcurrent faults